2020
DOI: 10.3906/sag-1908-87
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxy vitamin D level is associated with sleep disturbances in patients with chronic kidney disease on hemodialysis: a cross-sectional study

Abstract: Background/aim: Deficient levels of vitamin D are an important factor in the pathogenesis of some neurodegenerative diseases. The aim of this study is to determine the relationship between vitamin D deficiency and depression status and sleep disorders of patients on dialysis. Materials and methods: In this cross-sectional study, 121 hemodialysis patients were enrolled. All patients had been on hemodialysis for at least six months at the time of the study. Sleep quality and depression status were measured by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
0
5
0
1
Order By: Relevance
“…Hon et al and Yavuz et al approved that the levels of 25(OH) D fell down in dialysis patients having sleep disturbances, in comparison with those that do not have sleep disorders (6,15). However, they did not confirm whether the treatment of vitamin D deficiency could affect the quality of sleep.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hon et al and Yavuz et al approved that the levels of 25(OH) D fell down in dialysis patients having sleep disturbances, in comparison with those that do not have sleep disorders (6,15). However, they did not confirm whether the treatment of vitamin D deficiency could affect the quality of sleep.…”
Section: Discussionmentioning
confidence: 97%
“…Deficiency of vitamin D is commonly experienced by patients who undergo dialysis (6,11,12). Several studies reported the relationship of vitamin D deficiency and sleep disorders in non-dialysis (13,14) and dialysis patients (6,15). Also, according to several research works, vitamin D deficiency treatment improves sleep quality in non-dialysis patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, complications caused by hemodialysis, especially sleep disturbance, are often ignored ( 24 ). Studies have shown that there are many factors associated with sleep disturbance in MHD patients, such as gender, diet, depression and serum PTH levels ( 14 , 16 ). In this study, we found that age, Alb and Ca 2+ were independent risk factors for sleep disturbance in MHD patients, and confirmed that age, Alb and anxiety were associated with the severity of sleep disturbance in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that gender, age, education level, diabetes history, blood phosphorus level and depression are associated with the sleep quality of MHD patients ( 13 ). Another study has confirmed that compared with MHD patients with good sleep, there are more males, lower serum parathyroid hormone (PTH) and 25-hydroxy vitamin D levels, and a higher incidence of depression in patients with poor sleep, while there is no significant difference in age between groups ( 14 ). Although both studies showed that gender and depression were associated with sleep disturbance in MHD patients, there were differences in age.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that 25 (OH) D deficiency is an important risk factor for reducing sleep quality and the result is independent of other factors such as age, gender, depression, and the effect of hemodialysis [ 52 ]. Jean and coworkers showed that a daily dose of 10-30 mg of 25 (OH) D oral supplements completely resolves vitamin D deficiency in HD patients with high safety.…”
Section: Discussionmentioning
confidence: 99%